Qualidade fisiológica e sanitária de sementes de Solanaceae comercializadas em Juruti-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
Tomato and peppers have great potential for the agricultural and industrial sectors, requiring strict control over the production of seedlings. For this purpose, healthy seedlings are mainly associated with the use of high-quality seeds, as this allows them to express their productive potential, through the interaction of genetic, physical, health, and physiological components. Some factors can interfere with the quality of the seeds, such as the occurrence of microorganisms in the seeds and inadequate storage. To reduce the infestation of pathogens, pesticides have been used, however, the continued use of these products has caused concern for the environment and health of man, thus, research has sought alternative products for disease management, for example, the use of essential oils to treat seeds. Therefore, the objectives of this work were i) to evaluate the sanity and germination of tomato and pepper seeds marketed in Juruti, Pará; ii) to analyze the interference of essential oils in the germination of cherry tomato seeds. The experiments were divided into two chapters, the first being evaluating the health and germination of tomato and pepper seeds. Five cultivars of each were used, measuring: the percentage of germination, number of normal and abnormal seedlings, length of the aerial part, length of the radicle, dry mass of normal seedlings, the fresh mass of normal seedlings, germination speed index, average germination speed and incidence of pathogens. In chapter two, the interference of essential oils in the germination of cherry tomato seeds was evaluated, in which cherry tomato seeds and the essential oils of andiroba at 1% and copaíba at 1% were used. The variables were measured: percentage of germination, non-germinated seeds, normal seedlings, length of the shoot and root, germination index, and average germination speed. For the sanity and germination of tomato and pepper seeds, it was found that in the parameter’s germination, germination speed index, normal seedlings, length of the aerial part and root, the cultivars of “cayenne” pepper and “dedo de moça” pepper presented the lowest values, concerning other cultivars. Regarding the average germination speed, the “cayenne” cultivar presented the lowest value. The highest percentages of pathogen incidence were observed in the “dedo de moça” pepper cultivar. For the interference of andiroba and copaiba essential oils in the treatment of cherry tomato seeds, variables of germination percentage, normal seedlings, and shoot length did not show significant differences. The occurrence of pathogens in tomato and pepper seeds did not affect the physiological quality of the evaluated lots and the use of essential oils did not interfere with the germination of cherry tomato.
Keywords: Métodos Alternativos; Qualidade Fisiológica; Patogenecidade; CNPQ:: CIÊNCIAS AGRÁRIAS